2018
DOI: 10.1111/aogs.13509
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of monoamniotic twin pregnancies managed primarily in outpatient care—a Danish multicenter study

Abstract: Introduction:Monoamniotic twin pregnancies are high-risk pregnancies, and management by inpatient or frequent outpatient care is recommended. We report the outcomes of a national cohort of monoamniotic twin pregnancies managed primarily as outpatients. Material and methods:We prospectively analyzed the recorded data from the Danish Fetal Medicine Database, local databases, and medical records of all monoamniotic twin pregnancies diagnosed at the first trimester scan or later, and managed at the six major fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Prefumo et al reported on 16 MCMA twin pregnancies with no major abnormalities, recruited at < 16 weeks' gestation between 2004 and 2013; the rates of fetal loss and perinatal death were 37.5% and 10.0%, respectively 27 . Madsen et al, in a multicenter study from Denmark, reported on 46 MCMA twin pregnancies with no major abnormalities, recruited at < 17 weeks' gestation between 2004 and 2013; the rates of fetal loss and perinatal death were 26.1% and 11.8%, respectively 28 . Glinianaia et al used two multicenter datasets in England, which covered births between 2000 and 2013, to report on 61 MCMA twin pregnancies with no major abnormalities in which chorionicity had been determined by ultrasound at a median gestational age of 13 (IQR, 12-14) weeks; the rates of fetal loss and perinatal death were 18.9% and 12.1%, respectively 29 .…”
Section: Comparison With Findings From Previous Studiesmentioning
confidence: 99%
“…Prefumo et al reported on 16 MCMA twin pregnancies with no major abnormalities, recruited at < 16 weeks' gestation between 2004 and 2013; the rates of fetal loss and perinatal death were 37.5% and 10.0%, respectively 27 . Madsen et al, in a multicenter study from Denmark, reported on 46 MCMA twin pregnancies with no major abnormalities, recruited at < 17 weeks' gestation between 2004 and 2013; the rates of fetal loss and perinatal death were 26.1% and 11.8%, respectively 28 . Glinianaia et al used two multicenter datasets in England, which covered births between 2000 and 2013, to report on 61 MCMA twin pregnancies with no major abnormalities in which chorionicity had been determined by ultrasound at a median gestational age of 13 (IQR, 12-14) weeks; the rates of fetal loss and perinatal death were 18.9% and 12.1%, respectively 29 .…”
Section: Comparison With Findings From Previous Studiesmentioning
confidence: 99%
“…The search identified 505 articles, of which 152 were assessed with respect to their eligibility for inclusion (Table S1) and 15 were included in the systematic review ( Figure 1, Table 1). These 15 studies included 888 MCMA twin pregnancies, of which 44 (88 fetuses) were affected by TTTS [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . There was no randomized controlled trial comparing different management options (expectant vs laser vs cord occlusion vs amniodrainage) in MCMA twin pregnancies complicated by TTTS.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…GA, gestational age given as mean ± SD when more than one case of TTTS; NS, not specified. 11 Madsen (2019) 12 Anselem (2015) 13 Van Mieghem (2014) 14 Peeters (2014) 15 Murata (2013) 16 Suzuki (2013) 17 Morikawa (2012) 18 Baxi (2010) 19 Hack (2009) 20 Cordero (2006) 21 DeFalco (2006) 22 Heyborne (2005) 23 Demaria (2004) 24 Sau (2003) 25 Only first author's name is given. A study can be awarded a maximum of one star for each numbered item within selection and outcome categories.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Their complication rates, on the other hand, are extremely high. Indeed, studies reporting on the outcome of monoamniotic twin pregnancies from the first trimester onwards show them to have significantly higher risks than do dichorionic or diamniotic twin pregnancies, with fetal or neonatal loss rates of up to 20–50%. The majority of these losses occur prior to 24 weeks' gestation, but even thereafter, the risk of fetal death remains as high as 5–10%, which is double the risk seen in monochorionic diamniotic twins.…”
mentioning
confidence: 99%
“…In contrast to diamniotic twins, only about one‐third of fetal deaths in monoamniotic twins are due to twin reversed arterial perfusion sequence, twin–twin transfusion syndrome, preterm birth or (pregnancy termination for) congenital anomalies, while the other two‐thirds are thought to be the result of acute cord occlusion and/or intertwin transfusional imbalances as a consequence of the near‐universal cord entanglement and the large intertwin placental anastomoses seen in these pregnancies.…”
mentioning
confidence: 99%